Instantaneous isotropic volumetric imaging of fast biological processes - Wagner, Nils; Gierten, Jakob; Wittbrodt, Joachim (Nature methods, 2019)
Iso-LFM enables rapid, instantaneous volumetric imaging of biological processes with isotropic and improved resolution by simultaneously capturing orthogonal light fields.
Gesehen am 25.06.2019